Domestic violence during pregnancy and its predictive factors during the COVID-19 epidemic among primiparous women in Isfahan - Masomah Jalili; Shahnaz Kohan; Mohammad Javad Tarrahi; Fatemeh Torabi (Tehran University of Medical Sciences, 2023)
Background & Aim: COVID-19 is one of the crises that seriously threatens the individuals' mental health, especially pregnant women. On the other hand, the COVID-19 quarantine can affect the occurrence of domestic violence in pregnant women. The aim of the current study was to investigate the prevalence of domestic violence in pregnancy and the factors affecting it during the COVID-19 pandemic. Methods & Materials: This was a descriptive-correlational study conducted on 308 primiparous mothers referred to health centers in Isfahan in 2021. The participants were selected using the multi-stage sampling method. Data was collected using a demographic characteristics form and the domestic violence questionnaire. Data analysis was done through the SPSS software version 22 using the Spearman's correlation coefficient, Mann-Whitney and Kruskal-Wallis tests. Results: A total of 59 mothers (19.2%) experienced domestic violence during their pregnancy (a score of 60 and above from the domestic violence questionnaire). The most prevalent type of violence (including perceived) was psychological violence with 74.4% (229 people), followed by economic, sexual, and physical violence with 35.1% (108 people), 17.2% (53 people), and 14.9% (46 people) respectively. A significant relationship was found between domestic violence during pregnancy and the number of siblings, birth order, the educational level of mother and her husband, and husband's occupation (P<0.05). Conclusion: The COVID-19 pandemic has made pregnant women more vulnerable to domestic violence. There are many individual and cultural factors contributing to domestic violence. Some factors were identified as the predictors of violent behavior such as the educational level of woman and her husband, and occupation. Identifying these factors and screening of domestic violence during pregnancy can prevent the occurrence of violent behavior by the spouse and the negative consequences of domestic violence on the mother and her fetus.